Relativistic models of anisotropic superdense star in the regime of Karmarkar's condition. (23rd February 2023) - Parida, Bikram Keshari; Majumder, Shreya; Das, Shyam; Chakraborty, Koushik; Rahaman, Farook
Abstract: We obtained a new class of solutions for a relativistic anisotropic compact star by utilizing the Karmarkar embedding condition. To obtain the closed-form solution a suitable form of one of the gravitational potentials has been chosen to determine the other by analyzing the Karmarkar condition. The resulting solutions are found to be well-behaved and regular and could describe a compact stellar object. Considering the current estimated values of the mass and radius of the pulsar 4 U 1820 − 30 as input parameters, all the physically relevant parameters are shown to be well-behaved to a very good degree of accuracy.